Nitric oxide selectively depletes macrophages in atherosclerotic plaques via induction of endoplasmic reticulum stress - Martinet, W (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: Macrophages in atherosclerotic plaques have a tremendous impact on atherogenesis and plaque destabilization. We previously demonstrated that treatment of plaques in cholesterol-fed rabbits with the nitric oxide (NO) donor molsidomine preferentially eliminates macrophages, thereby favouring features of plaque stability. In this study, we investigated the underlying mechanism. EXPERIMENTAL APPROACH: Macrophages and smooth muscle cells (SMCs) were treated in vitro with the NO donors, spermine NONOate or S-nitroso-N-acetylpenicillamine (SNAP) as well as with the well-known endoplasmic reticulum (ER) stress inducers thapsigargin, tunicamycin, dithiothreitol or brefeldin A. Cell viability was analysed by Neutral Red viability assays. Cleavage of caspase-3, DNA fragmentation and ultrastructural changes were examined to characterize the type of macrophage death. Induction of ER stress was evaluated by measuring C/EBP homologous protein (CHOP) expression, phosphorylation of eukaryotic initiation factor 2α (eIF2a), splicing of X-box binding protein 1 (XBP1) and inhibition of protein synthesis. KEY RESULTS: Macrophages and SMCs treated with spermine NONOate or SNAP showed several signs of ER stress, including upregulation of CHOP expression, hyperphosphorylation of eIF2α, inhibition of de novo protein synthesis and splicing of XBP1 mRNA. These effects were similar in macrophages and SMCs, yet only macrophages underwent apoptosis. Plaques from molsidomine-treated atherosclerotic rabbits showed a 2.7-fold increase in CHOP expression as compared to placebo. Beside NO, selective induction of macrophage death could be initiated with thapsigargin and tunicamycin. CONCLUSIONS AND IMPLICATIONS: Induction of ER stress explains selective depletion of macrophages in atherosclerotic plaques by a NO donor, probably via inhibition of protein synthesis.